Bitter Taste Receptors and Chronic Otitis Media. (August 2021) - Kaufman, Adam C.; Colquitt, Lauren; Ruckenstein, Michael J.; Bigelow, Douglas C.; Eliades, Steven J.; Xiong, Guoxiang; Lin, Cailu; Reed, Danielle R.; Cohen, Noam A.
Objective: To evaluate the presence of bitter taste receptors (T2Rs) in the middle ear and to examine their relationship with chronic ear infections. Study Design: Cross-sectional study. Setting: Tertiary care hospital. Methods: This study enrolled 84 patients being evaluated for otologic surgery: 40 for chronic otitis media (COM) and 44 for other surgical procedures (controls). We collected a small piece of mucosa from 14 patients for mRNA analysis and from 23 patients for immunohistochemistry. A total of 55 patients underwent a double-blind taste test to gauge sensitivity to phenylthiocarbamide, denatonium, quinine, sucrose, and sodium chloride; 47 patients gave a salivary sample for single-nucleotide polymorphism analysis of rs1376251 ( TAS2R50 ) and rs1726866 ( TAS2R38 ). Results: Bitter taste receptors were found in all samples, but the repertoire varied among patients. T2R50 was the most consistently identified receptor by mRNA analysis. Its rs1376251 allele was related to susceptibility to COM but not the expression pattern of T2R50. Ratings of bitterness intensity of phenylthiocarbamide, a ligand for T2R38, differed significantly between the COM and control groups. Conclusion: T2Rs were found within the middle ear of every patient sampled; the rs1376251 allele of TAS2R50 appears to be related to chronic ear infections. These receptors are an intriguing target for future research and possible drug targeting.